Association between obesity and dental caries among adolescents in UAE: a pilot cross sectional study - Awad, Manal; Bani Issa, Wegdan; Radwan, Hadia; Fakhry, Randa; Al-Yateem, Nabeel; Rossiter, Rachel (Frontiers in Oral Health, 2023)
Background: Obesity and dental caries among adolescents is a growing worldwide public health issue. They share some common and modifiable influences. The objective of this study was to evaluate the association between obesity and dental caries among adolescents in the United Arab Emirates (UAE). Methods: This pilot cross-sectional study enrolled 161 adolescents 13-19 years old from private and public schools in the UAE. Participants were classified as normal weight, overweight or obese. Dental caries was diagnosed according to the criteria recommended by the World Health Organization (WHO). Independent t-tests were used to compare average number of decayed, filled and missing surfaces (DMFS) by age, sex, school type, mothers’ employment, BMI categories, waist circumference, oral health habits and plaque index. Additionally, a multiple linear regression model was applied to analyze the association between BMI, waist circumference and dental caries, adjusted for confounding factors considered in this study. Results: The average age of the participants was 16.2 ± 1.4. The prevalence of overweight/obesity was 42% (N=68) measured by BMI. Overall the average DMFS score was 4.35 ± 4.5, with significantly lower dental caries rates among girls ((3.3 (SD:4.0)) than boys (6.7 (SD:3.4), (p <0.05). The linear regression model revealed that, being a male, attending a public school and having average waist circumference were all positively and significantly associated with dental caries (p <0.05). Conclusion: Obesity measured by waist circumference was significantly associated with dental caries among adolescents in the UAE. Further research is required to investigate the complex association between obesity and dental caries and how dietary habits, oral hygiene habits, and parental socioeconomic status mediate the association between obesity and dental caries.